Pengaruh Ekstrakurikuler dan Motivasi Belajar terhadap Hasil Pembelajaran Mahasiswa STIE AAS Surakarta - Dewi Muliasari; Gunawan Setyadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
The research aims to analyze the influence of English Fun Club extracurricular and learning motivation on the learning outcomes of Bahasa Inggris 2 subject of STIE AAS Surakarta students. It is assumed that the significant different in the students daily scores and semester scores is influenced by these two variables. This research is a quantitative approach using population study or census. The population of this research is the fourth semester students of STIE AAS Surakarta who take part in the English Fun Club activities, totaling 67 people in the odd semester of the 2020/2021 academic year and all of them are taken as research subjects. The data collection techniques using documentation and questionnaires. The instrument validity is tested using Product Moment and the reliability is tested using Cronbach Alpha. The data is analyzed using multiple linear regress analysis. Based on the interpretation of correlation coefficient and tested using product moment correlation formula, the results is 0.693 which proves that extracurricular activities have positive influence on learning outcomes. While the results of the partial calculation of the influence of learning motivation on the learning outcomes with regression coefficient value (b) 0.663, at a significance level of 5%, the tcount is 9.984 with a significance value of 0.000. The regression coefficient has positive value and a significance value (p) <0.05, it can be concluded that there is positive influence of learning motivation on English learning outcomes for STIE AAS Surakarta students.